Protocol for a randomized controlled trial of patient–portal–based screening for substance use among people with HIV - Roessler, Eric; Zimmer, Daniela; Grant, Jon; Pollack, Harold; Boodram, Basmattee; Schmitt, Jessica; Friedman, Eleanor; Pagkas-Bather, Jade; Brewer, Russell A.; Ridgway, Jessica; Laiteerapong, Neda (Frontiers in Public Health, 2025)
BackgroundAchieving Equity in Patient Outcome Reporting for Timely Assessments of Life with HIV and Substance Use (ePORTAL HIV-S) is a research project funded by the National Institute for Drug Abuse to implement and evaluate multi-level interventions to decrease barriers to substance use screening and treatment for PLWH. At its center is a multidomain intervention addressing digital, sociocultural, and health care system environments, at individual, interpersonal, and community levels. ePORTAL HIV-S has four overall goals; this manuscript describes the protocol specifically for the randomized control trial (RCT) portion of the study. To provide additional context, we briefly describe the overall ePORTAL HIV-S project.MethodsThis project will utilize a culturally tailored approach to increase patient portal use among PLWH in our health system via a community health worker (CHW)-led initiative. This will lay the groundwork for the second aim, the focus of the current manuscript, RCT to measure the effectiveness of a population health, patient portal-based substance use screening program. Approximately 880 people will be enrolled and randomized 1:1 to intervention vs., control arms. Participants in the control arm will receive usual care (substance use screening during clinic visits), whereas the intervention arm will be invited to complete substance use screening via the patient portal as well as during clinic visits as per usual care. The primary outcome will be the percentage of people screened for substance use. ePORTAL will also implement a collaborative care model to both connect patients who screen positive for SUD to care and effectively treat PLWH. Finally, we will plan for dissemination of ePORTAL HIV-S to other sites that provide care for PLWH.DiscussionSUD disproportionately impacts PLWH which leads to negative health outcomes. This novel approach will incorporate the privacy and convenience of patient portal screening with screening during routine clinic visits.Clinical trial registrationclinicaltrials.gov, identifier NCT06682468.